2015
DOI: 10.1002/hed.24258
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p16 expression in Epstein‐Barr virus–positive nasopharyngeal carcinomas

Abstract: Background Overexpression of p16 is associated with improved outcomes among patients with oropharyngeal carcinoma. However, its role in nasopharyngeal cancer patient outcomes remains unclear. Methods Eighty-six patients with nasopharyngeal carcinoma treated at MD Anderson from 2000 to 2014 were identified. Epstein bar virus (EBV) and Human papillomavirus (HPV) status were determined by in situ hybridization and p16 by immunohistochemical staining. Results EBV positivity was associated with extended overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…The HPV+ tumors were found only in white individuals, and there was a strong association with cigarette smoking . Jiang et al investigated 86 patients with NPC who were treated at The University of Texas MD Anderson Cancer Center in Houston between 2000 and 2014 and reported that p16 overexpression was found to be associated with improved progression‐free survival and locoregional control in patients with EBV+ NPC; they concluded that p16 expression may complement EBV status in predicting treatment outcomes for patients with NPC . Data from the nonendemic countries of Asia also demonstrated that HPV/p16 expression is uncommon in patients with NPC .…”
Section: Discussionmentioning
confidence: 99%
“…The HPV+ tumors were found only in white individuals, and there was a strong association with cigarette smoking . Jiang et al investigated 86 patients with NPC who were treated at The University of Texas MD Anderson Cancer Center in Houston between 2000 and 2014 and reported that p16 overexpression was found to be associated with improved progression‐free survival and locoregional control in patients with EBV+ NPC; they concluded that p16 expression may complement EBV status in predicting treatment outcomes for patients with NPC . Data from the nonendemic countries of Asia also demonstrated that HPV/p16 expression is uncommon in patients with NPC .…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Because programmed death-ligand 1 (PD-L1) is frequently overexpressed in many types of human cancers, 13 the PD1/ PD-L1 axis is thought to be one of the mechanisms by which cancer cells escape immune surveillance. [16][17][18] However, very little is known about the precise differences in the tumor immune microenvironments of patients with NPC with EBV and without EBV infection. 14,15 In addition, an EBV infection, which increases the PD-L1 expression, has been shown to improve the prognosis in patients with NPC.…”
Section: Introductionmentioning
confidence: 99%
“…12 Studies from both endemic and nonendemic regions have reported the occurrence of HPV in NPC tumors, with or without the coexistence of EBV. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Unlike in oropharyngeal carcinoma, 32 no statistical significance for outcome has been attributed to HPV in NPC with 1 exception: Dogan et al reported that patients with HPV-positive tumor had, similarly to the patients with EBVpositive tumor, significantly better overall survival (OS) than the patients with EBV/HPV-negative tumor. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In addition, Jiang et al suggested that although overexpression of p16 is not a significant prognostic marker for OS in NPC, it correlates with better progression-free survival and locoregional control in patients with EBV-positive tumor.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In addition, Jiang et al suggested that although overexpression of p16 is not a significant prognostic marker for OS in NPC, it correlates with better progression-free survival and locoregional control in patients with EBV-positive tumor. 22 Previous studies on viral infections in NPC have mainly reported on small and heterogeneous series of patients treated at 1 or 2 institutions. Thus, data on the prognostic value of EBV and HPV in NPC are limited.…”
mentioning
confidence: 99%